(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Abstract The district of Diamantina/MG received, in 1999, the title of Cultural Heritage of Humanity due to its historical, cultural and natural wealth. The city emerged from the discovery of mineral deposits by the “bandeirantes” and, even after the decline of diamond mining, it maintained plight with the refinement of a social life refined by good customs arising from the taste for theater, for art, also expressed in architecture. and in music. In addition to its cultural diversity there is also a natural exuberance that spreads through the region through rivers, waterfalls, caves and termal waters. And in this context, the Federal University of Vales do Jequitinhonha e Mucuri-UFVJM is inserted, initially created by Juscelino Kubitschek with the Faculty of Dentistry of Diamantina-FAOD. Therefore, due to the fact that a significant portion of the incoming students do not reside in the district, it was perceived the need to present the city and its history, through a guided tour, providing the opportunity for knowledge and, consequently, respect for this cultural and natural heritage. In this sense, the present work has the purpose of providing the student entering the Federal University of Vales do Jequitinhonha e Mucuri-UFVJM, in Diamantina/MG, knowledge about the city’s history and heritage through a cultural tour of the historic center, through an extension project in partnership with the pro-rectory. The methodological form stems from a review of literature and documents on heritage, heritage education and related topics, as well as a qualitative-quantitative research through the application of a semi-open questionnaire with the objective of monitoring the evolution in relation to the participation and interest of students and to understand the satisfaction and effectiveness of the project. In this way, the study suggests the need to present the extension project "Giro cultural: knowing our heritage" through the history of Diamantina and the knowledge of its main tourist attractions, as well as the city’s infrastructure with regard to hospitals, health centers, public services, among others that may be of need and interest to the student, in addition to promoting the integration of the student community and freshmen, combining actions of reception and socialization. Finally, the effectiveness of the action is perceived, in view of the positive result of the evaluations regarding the initiative of the proposal and the satisfaction of the participants for the knowledge acquired through the cultural tour. Keywords: Extension Project. History. Patrimony. Diamond.